Extreme Maternal Metabolic Acidosis Leading to Fetal Distress and Emergency Caesarean Section - Nicolas Cecere; Corinne Hubinont; Arnauld Kabulu Kadingi; Marie-Françoise Vincent; Peter Van den Bergh; Anna Onnela; Philippe Hantson (Case Reports in Obstetrics and Gynecology)
A 31-year-old pregnant woman ( weeks) was admitted with extreme tachypnea. She had a previous history of congenital muscular dystrophy (Ullrich’s disease) and isolated glucosuria. The patient had reduced food intake during the last 24 hours prior to admission and vomited twice. Serum glucose level was normal (112 mg/dL), while urinalysis revealed glucosuria 4+ and ketonuria 4+. ABG revealed pH 7.06, PCO2 9 mm Hg, and bicarbonate 2 mmol/L. Anion gap was 28 mmol/L. Tachypnea was a compensatory mechanism for a severe nonlactic metabolic acidosis. The diagnosis of starvation ketoacidosis was established. The patient received supplemental dextrose 10% intravenously and sodium bicarbonate. As fetal heart monitoring was pathological, an emergency caesarean section was performed. Umbilical cord venous pH was 7.01, with PCO2 34 mm Hg and bicarbonate 8 mmol/L. Starvation ketoacidosis is a rare metabolic disorder that may occur mainly in the third trimester of pregnancy. Muscular dystrophy and renal glucosuria were precipitating factors.